Genetic Variability and Heritability of Vegetative Growth Variables in 41 Cayenne Pepper Cultivars - Saputra, Pringky Okta; Herison, Catur; Rustikawati, Rustikawati; Nurjanah, Uswatun; Ganefianti, Dwi Wahyuni; Sukisno, Sukisno (Badan Penerbitan Fakultas Pertanian (BPFP), 2025)
This study aimed to estimate genetic and phenotypic variability, as well as heritability values, in 41 Cayenne pepper cultivars based on vegetative traits. The research was conducted from May to October 2024 at the Experimental Farm of the Faculty of Agriculture, University of Bengkulu, situated in Beringin Raya village, Bengkulu City, at an elevation of 10 m above sea level. A Randomised Complete Block Design (RCBD) was employed with a single factor consisting of 41 cultivars with three replications, each comprising 20 plants per replication. The results revealed a wide range of genetic variability for traits such as plant height, first dichotomous height, number of leaves, leaf area, leaf greenness, number of dichotomous points, canopy area, stem diameter, shoot fresh weight, and shoot dry weight. High phenotypic variability was observed across all evaluated traits. High heritability was found in the trait of first dichotomous height. Moderate heritability was observed for plant height, number of leaves, leaf greenness, number of dichotomous points, canopy area, shoot fresh weight, and shoot dry weight. Low heritability was detected in leaf area, stomatal density, and stem diameter.